Nanofabricated Bacterial Cell Walls with Intrinsic Peroxidase‐Mimicking and Sonodynamic Activities for Cancer Combination Treatment - Meng Yang; Yang Meng; Junling Li; Liya Bai; Yuanyuan Cheng; Yuanyuan Liu; Mingxin Cao; Xiaoying Yang; Yinsong Wang; Yang Liu (Advanced Science)
Abstract Bacterial cancer therapy recently has been attracting more and more attention because of its multiple functions to fight cancer. Porphyromonas gingivalis (Pg), a Gram‐negative pathogenic bacterium, acquires protoporphyrin IX (PpIX) and iron from heme and synthesizes abundant µ‐oxo bisheme on its cell walls (CWs). For the first time, it is found that the CWs extracted from Pg has intrinsic peroxidase (POD)‐mimicking and sonodynamic activities owing to the presence of µ‐oxo bisheme. In this study, the CWs of Pg are nanofabricated to form the CW vesicles (CWV) containing a large amount of lipopolysaccharide (LPS) and further encapsulated doxorubicin (DOX) to prepare DOX‐loaded CWV (DOX@CWV), hoping to eradicate cancer by combining sonodynamic therapy (SDT), chemotherapy, and bacterial immunotherapy. The results confirmed that DOX@CWV can catalyze the conversion of H2O2 into O2 and consume the reduced glutathione (GSH), and thus greatly boost their own sonodynamic performance upon ultrasonic irradiation. Both in vitro and in vivo, DOX@CWV efficiently inhibited cancer growth by combining SDT and chemotherapy, and also exerted synergistic anticancer immune effects of bacterial immunotherapy and SDT. In summary, the findings not only contribute a promising bacterial therapeutic agent but also provide a combination strategy for clinical cancer treatment.